Anti-Fn14 Antibody-Conjugated Nanoparticles Display Membrane TWEAK-Like Agonism - Ahmed Aido; Olena Zaitseva; Harald Wajant; Matej Buzgo; Aiva Simaite (MDPI AG, 2021)
Conventional bivalent IgG antibodies targeting a subgroup of receptors of the TNF superfamily (TNFSF) including fibroblast growth factor-inducible 14 (anti-Fn14) typically display no or only very limited agonistic activity on their own and can only trigger receptor signaling by crosslinking or when bound to Fcγ receptors (FcγR). Both result in proximity of multiple antibody-bound TNFRSF receptor (TNFR) molecules, which enables engagement of TNFR-associated signaling pathways. Here, we have linked anti-Fn14 antibodies to gold nanoparticles to mimic the "activating" effect of plasma membrane-presented FcγR-anchored anti-Fn14 antibodies. We functionalized gold nanoparticles with poly-ethylene glycol (PEG) linkers and then coupled antibodies to the PEG surface of the nanoparticles. We found that Fn14 binding of the anti-Fn14 antibodies PDL192 and 5B6 is preserved upon attachment to the nanoparticles. More importantly, the gold nanoparticle-presented anti-Fn14 antibody molecules displayed strong agonistic activity. Our results suggest that conjugation of monoclonal anti-TNFR antibodies to gold nanoparticles can be exploited to uncover their latent agonism, e.g., for immunotherapeutic applications.